A Pilot Proteomic Analysis of Huntington’s Disease by Functional Capacity - Andrew McGarry; Ruin Moaddel (Brain Sciences)
Background: The molecular biology of Huntington’s Disease (HD) has grown substantially, with pathological considerations extending to genetic modifiers, epigenetic changes, transcriptomics, the proteome, and the metabolome. The metabolome and proteome are especially intriguing in that they most directly reflect the functional state of the cellular environment, which may involve some combination of pathology as well as compensation. Methods: We assessed CSF proteomics from eight participants by their functional severity (TFC range 3–13), with 47 proteins having a minimum r-value of 0.7 and nominal p-values < 0.05. Results: Our exploratory data reveal correlations between progression and several processes including inflammation, ECM homeostasis and NAD+ metabolism. Conclusions: Consistently identified targets that correlate with phenotype or progression may have value, if validated, as enrichment tools in clinical trials and potentially as markers of therapeutic response.